Olefin selectivity of K-Mn promoters on CoFe-ZSM-5 based catalyst in CO2 hydrogenation - Maseko, Paula; Cele, Mduduzi N.; Mdleleni, Masikana M. (Frontiers in Chemistry, 2025)
The conversion of carbon dioxide (CO2), a major greenhouse gas, into light olefins is crucial for mitigating environmental impacts and utilizing non-petroleum-based feedstocks. Thermo-catalytic CO2 transformation into valuable chemicals offers a promising solution to this challenge. This study investigates the effect of potassium (K) and manganese (Mn) promoters on CO2 conversion and C2H4 selectivity over CoFe-ZSM-5 zeolites. Structural characterization via FTIR, pyridine-FTIR, and PXRD confirmed the successful incorporation of K and Mn into CoFe-ZSM-5 at 80°C without significant structural changes to the zeolite framework. BET analysis revealed that metal incorporation did not substantially alter the surface area, while SEM and TEM analyses confirmed the preservation of ZSM-5 spherical morphology. Fixed-bed reactor experiments conducted at 350°C and 20 bar demonstrated that K and Mn synergistically enhanced CO2 conversion efficiency and selectivity toward C2H4. The K-Mn/4Fe4Co-ZSM-5 catalyst (modified with 4% Co and 4% Fe) exhibited the highest performance, achieving 97% olefin selectivity. Furthermore, Mn and K promoters reduce the CO selectivity on the Co-Fe-ZSM-5 catalyst. These findings underscore the critical role of K and Mn in facilitating efficient CO2 activation and directing the reaction pathway toward valuable olefin products.